2012
DOI: 10.1068/p7350
|View full text |Cite
|
Sign up to set email alerts
|

Creativity, Ambiguous Figures, and Academic Preference

Abstract: Abstract. Research suggests that ambiguous figure reversal is associated with creativity, but current evidence relies on subjective self-report that is difficult to quantify (Wiseman, Watt, Gilhooly, Georgiou, 2011 British Journal of Psychology 102 615-622). Using quantifiable measures of both phenomena we confirm this claim. We also find that participants studying science experience much more frequent reversal-a novel and intriguing finding.Keywords: ambiguous figure reversal, creativity, academic preference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…They confirmed this link, finding a close relationship between the frequency of reversals and divergent thinking fluency in typically developing adolescents and adults. This finding has since been replicated by Doherty and Mair (2012). The ability to reverse ambiguous figures relies on the executive function of inhibition in normal development (Wimmer and Doherty 2011) and on working memory (Intaite et al 2014).…”
Section: Introductionmentioning
confidence: 70%
“…They confirmed this link, finding a close relationship between the frequency of reversals and divergent thinking fluency in typically developing adolescents and adults. This finding has since been replicated by Doherty and Mair (2012). The ability to reverse ambiguous figures relies on the executive function of inhibition in normal development (Wimmer and Doherty 2011) and on working memory (Intaite et al 2014).…”
Section: Introductionmentioning
confidence: 70%
“…In sum, these correlations between idiosyncratic switching patterns, individual personality traits and neurotransmitter profiles are compatible with the observed temporal stability of switching patterns, as these stable characteristics may influence the perceptual processing of multi-stable auditory stimuli. High creativity has been found to be related to increased switching in ambiguous figures (Doherty and Mair, 2012;Wiseman et al, 2011), but was found to be unrelated to individual differences in auditory streaming (Farkas et al, 2016a). However, there is a lack of consensus both in the definition (Kozbelt et al, 2010) and in the assessment (Plucker and Mackel, 2010) of creativity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Experiment 2 the first phase duration for image D2 (street map-flag pole, see Figure 5) is longer than for other images in the same experiment, suggesting that this image is processed differently. Previous studies that examined the connection between creativity and perceptual switching overlooked the role of different types of images (Doherty & Mair, 2012;Laukkonen & Tangen, 2017;Wiseman et al, 2011;Wu et al, 2016). It is possible that the relation between perceptual switching and creativity is found only for some images.…”
Section: Discussionmentioning
confidence: 99%
“…They also found a strong correlation between self-reported ease of perceptual switching and categorical flexibility measured with a single item unusual uses task. Following up on these results, Doherty and Mair (2012) found that fluency for written responses measured with the Pattern Meanings task (Wallach & Kogan, 1965, p. 33) is positively correlated with the number of switches in perceptual multistability tasks (duck-rabbit, vase-face, Necker cube). The authors speculated that the same executive control mechanisms may be involved in perceptual switching and divergent production, therefore the relationship is worth exploring further.…”
Section: Introductionmentioning
confidence: 91%